An Efficient Approach for Secure Storage, Search using AES in Cloud Storage - Anjaiah, P; Raghavendra, C; Rajendra Prasad, K (International Journal of Engineering and Technology, 2018)
The expanded rate of development and adaption of distributed computing, day by day, more delicate data is being brought together onto the cloud. For the security of profitable data, the information must be encoded before externalization. The current inquiry procedures enable the client to seek over encoded information utilizing keyword yet these methods represent just correct hunt. There is no resilience for grammatical errors and organization irregularities which are typical client conduct. This makes compelling information stockpiling and use an exceptionally difficult errand, providing client seeking extremely baffling and wasteful. In this paper, we concentrate on secure capacity utilizing Advanced Encryption Standard (AES) and data recovery by performing Fuzzysearch on information which is scrambled while transferring on the cloud. We are proposing the execution of a progressed Fuzzykeywordtechnique called the Wildcard based procedures which restores the coordinating records when clients seeking inputs definitely coordinate the predefined keyword or the nearest conceivable coordinating documents in light of likeness catchphrase semantics when correct match comes up short. In the proposed method, using alter separation to measure keywords similitude and build up a proficient strategies for developing fuzzy keyword sets, which concentrate on diminishing the capacity and portrayal overtop. Â Â